Community involvement in safeguarding intangible cultural heritage: Case study of Malacca - Abu Bakar, Aisyah; Mohamed Osman, Mariana; Bachok, Syahriah (IIUM Press, 2017)
This study intends to assess the influence of universal culture on local culture, which is reflected in community manifestation of Intangible Cultural Heritage (ICH) in a World Heritage Site (WHS). The concerned community of the study is the cultural community of Malacca who are residing within the core zone and buffer zone of WHS location of Malacca. Since the physical setting of the WHS location is a rapidly urbanizing tourism city, it is unsurprising that the locals of the city are experiencing the impact of urbanization which often associates to modernization and globalization. As the community assimilates into the global mainstream of society, the distinctiveness of their local culture slowly disappears as universal culture gradually disseminates into the lives of the community. The unfavorable influence of universal culture results in common yet alarming universal community issues facing community manifestation of ICH. The community issues weaken social coherence of the community members to safeguard their endangered and declining ICH. As a result, cultural identity of the community deteriorates and cultural diversity of the WHS will potentially be at a loss. The study recognizes the community issues through the interaction between universal traits of the community with their manifestation of ICH. Universal traits are the commonly analyzed demographic and socioeconomic factors which represent the concept of diversity of the members in the cultural community. The analysis determines the statistical interactions between universal traits and community manifestation of ICH in relation to the recognized community issues from literature reviews.